2014
DOI: 10.7554/elife.03025
|View full text |Cite
|
Sign up to set email alerts
|

Integrated action of pheromone signals in promoting courtship behavior in male mice

Abstract: The mammalian vomeronasal organ encodes pheromone information about gender, reproductive status, genetic background and individual differences. It remains unknown how pheromone information interacts to trigger innate behaviors. In this study, we identify vomeronasal receptors responsible for detecting female pheromones. A sub-group of V1re clade members recognizes gender-identifying cues in female urine. Multiple members of the V1rj clade are cognate receptors for urinary estrus signals, as well as for sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
136
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(145 citation statements)
references
References 54 publications
9
136
0
Order By: Relevance
“…Female estrous state has an important influence on the reproductive behaviors of male mice, notably via olfactory cues (e.g., Dixon and Mackintosh 1975;Haga-Yamanaka et al 2014;Ingersoll and Weinhold 1987;Jakupovic et al 2008). In terms of vocal behavior, we have found that male mice show subtle shifts in the spectrotemporal structure of their USVs across the estrous phases of their female partners (Hanson and Hurley 2012).…”
Section: Discussionmentioning
confidence: 77%
“…Female estrous state has an important influence on the reproductive behaviors of male mice, notably via olfactory cues (e.g., Dixon and Mackintosh 1975;Haga-Yamanaka et al 2014;Ingersoll and Weinhold 1987;Jakupovic et al 2008). In terms of vocal behavior, we have found that male mice show subtle shifts in the spectrotemporal structure of their USVs across the estrous phases of their female partners (Hanson and Hurley 2012).…”
Section: Discussionmentioning
confidence: 77%
“…Instead they tend to be a species-specific multi-component combination of molecules [5,10]. For example, in the house mouse, sulfated oestrogens and a particular fraction of female urine form a multi-component mouse pheromone, produced by oestrous females, which promotes male mounting [10,11]. Most pheromones are detected by the sense of smell.…”
Section: Pheromones Are Chemical Signals That Meet Well-established Cmentioning
confidence: 99%
“…Mechanisms that underlie such coordination are better understood in females. For example, ovulating female mice release pheromones to attract males (Haga-Yamanaka et al, 2014), and juvenile females lacking mature gametes release a peptide pheromone to inhibit male courtship behavior (Ferrero et al, 2013). In addition, the ability of female mice to detect attractive male pheromones depends on the ovulation status signaled by a sex hormone (Dey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%